Prenatally detected non-immune atrioventricular block and maternal arrhythmia - case presentation and literature review - Michalak, Arkadiusz; Witczak, Marta; Kukawczyńska, Elżbieta; Niwald, Marek; Respondek-Liberska, Maria (Prenatal Cardiology, 2016)
Our clinical report describes a rare finding of a prenatally-detected congenital atrioventricular (AVB) block without associated maternal antibodies, which progressed from 1st/2nd degree AVB to complete heart block during second half of pregnancy. Obstetrical ultrasound at 12th week did not reveal any abnormalities and prenatal echocardiography (due to VSD in afamily member) at the 18th week of gestation detected 1st degree block, then bigeminy and bradycardia. Transplacental treatment with B-2-mimetics was introduced. The delivery was organized in a tertiary center and a pacemaker for the newborn baby was secured and implanted in 15th day of life. Currently the boy`s condition is good and stable. Before therapy with B-2-mimetics the mother underwent echocardiography and ECG which revealed clinically silent structural and conduction heart abnormalities. Literature findings suggest that parents of children with non-immune congenital or childhood AVB are more likely to carry clinically silent conduction abnormalities than general population. Given the corresponding findings in the mother and her son, they should be good candidates for genetic testing.